Analysis of Sugars from the Seeds of Tecoma urgentia - Sreedevi, E.; Rao, J.T. (Asian Journal of Chemistry, 2010)
Polysaccharides like galactose, mannose and reducing sugars have been analysed from the seeds of Tecoma urgentia. The seeds have high nutritional value.